Pattern of Drug Use and Associated Behaviors Among Female Injecting Drug Users From Northeast India: A Multi-Centric, Cross-Sectional, Comparative Study. (24th August 2015) - Ambekar, Atul; Rao, Ravindra; Agrawal, Alok; Goyal, Shrigopal; Mishra, Ashwani; Kishore, Kunal; Mukherjee, Debashis; Albertin, Cristina
Abstract : Background : Studies from developed countries document the presence of injecting drug use among females and significantly higher vulnerabilities and risks as compared with male injecting drug users (IDUs). Studies comparing vulnerabilities and drug use patterns between female and male IDUs are not available for developing countries. Objectives : The aim of the study was to assess the drug use pattern and related HIV vulnerabilities among female IDUs and compare these findings with those from male IDUs from four states of Northeast India. Method : The study used data collected as part of a nationwide study of drug use pattern and related HIV vulnerabilities among IDUs. Ninety-eight female and 202 male IDUs accessing services from harm reduction sites across the four states of Northeast region of India were chosen through random sampling methodology. Drug use pattern, injecting practices, and knowledge of HIV were assessed using a structured questionnaire. Results : Significantly higher proportion of female IDUs was uneducated, unemployed, reported their occupation as sex workers, and switched to injecting drug use faster as compared with male IDUs. Female IDUs practicing sex work differed significantly from those who did not with respect to frequency of daily injections, choice of drugs injected, and concomitant use of non-injecting drugs. More than half of female IDUs initiated sharing within the first month of injecting. Conclusions : The study demonstrates that female IDUs differ from male IDUs in their drug use pattern, initiation into injection as well as injecting behavior, which would be an important consideration during designing of female-specific interventions.